BIOLOGICAL ACTIVITY OF VIOLA ODORATA LINN AGAINST MYCOBACTERIUM TUBERCULOSIS - FAIZA HASSAN,; ISMAT NAEEM, (International Journal of Pharma and Bio Sciences, 2014)
In the present study the antibacterial activity of extracts and pure constituents of V. odorata was evaluated against Mycobacterium tuberculosis H37Rv and clinical isolate of MDR-TB (M. avium, ATCC 25291). Crude ethanol extract of the plant was fractionated with different solvents to yield respective extracts. The n-hexane and Dichloromethane fractions showing good activity against both strains were purified by chromatographic techniques and prep-HPLC to yield several pure compounds characterized by LCMS. Seven isolated pure compounds were assayed against M. tuberculosis H37Rv and MDR-TB isolate in different concentrations and their MIC’s were recorded. Same concentrations were taken in case of MDR-TB isolate. Of the seven pure isolates two compound; salicin and phenyl alanine ethyl ester were reported in this plant as a new source. The structure of these compounds was established by comparison of spectral data with the one reported earlier. Results suggested that V. odorata contained very active compounds against M. tuberculosis H37Rv and M. avium which can be used as lead for potential anti-TB drug formulations on further clinical trials. Ethno-medicinal use of V. odorata by local Hakims for treating lung related problems was also supported.